Vest Chest Physiotherapy Airway Clearance is Associated with Nitric Oxide Metabolism - Joseph H. Sisson; Todd A. Wyatt; Jacqueline A. Pavlik; Pawanjit S. Sarna; Peter J. Murphy (Pulmonary Medicine)
Background. Vest chest physiotherapy (VCPT) enhances airway clearance in cystic fibrosis (CF) by an unknown mechanism. Because cilia are sensitive to nitric oxide (NO), we hypothesized that VCPT enhances clearance by changing NO metabolism. Methods. Both normal subjects and stable CF subjects had pre- and post-VCPT airway clearance assessed using nasal saccharin transit time (NSTT) followed by a collection of exhaled breath condensate (EBC) analyzed for NO metabolites (). Results. VCPT shorted NSTT by 35% in normal and stable CF subjects with no difference observed between the groups. EBC concentrations decreased 68% in control subjects after VCPT (before = 115 ± 32 μM versus after = 37 ± 17 μM; ). CF subjects had a trend toward lower EBC . Conclusion. We found an association between VCPT-stimulated clearance and exhaled levels in human subjects. We speculate that VCPT stimulates clearance via increased NO metabolism.